Pengaruh Perceived Quality, Brand Awareness dan Brand Loyalty terhadap Customer Satisfaction dan Customer Value melalui Brand Equity pada Motor Sport Yamaha V-ixion - M Dudi Abdullah S. (JURNAL CITRA WIDYA EDUKASI, 2018)
Perceived Quality, Brand Awareness, Brand Loyalty to Customer Satisfaction and Customer Value through Brand Equity. The research was conducted through the methods of structural equation model (SEM) using LISREL program version 8.8. The number of respondents who researched many as 124 respondents in Jakarta through Yamaha motorsport V-ixion community by filling a questionnaire that has been provided. The research was conducted through a causal relationship between exogenous variables on endogenous variables. Result of the research are: a) Effect of the Perceived Quality, Brand Awareness, Brand Loyalty to Brand Equity shows the t-value of more than 2.05; b) Effect of the Brand Equity to Customer Satisfaction shows the t-value of 5.27; c) Effect of the Brand Equity to Customer Value shows the t-value of 3.46; and d) The effect Customer Satisfaction to Customer Value shows the t-value of 3,59. The influence of exogenous variables on endogenous variables showed a greater than T-table 1,96. Brand Equity has bigger effect to Customer Satisfaction than others. This shows a significant positive effect among Perceived Quality , Brand Awareness, Brand Loyalty to Customer Satisfaction and Customer Value through Brand Equity.